2018
DOI: 10.1080/09546634.2018.1441486
|View full text |Cite
|
Sign up to set email alerts
|

Liposuction-assisted circumferential trimming in treatment of axillary osmidrosis (AO)

Abstract: The liposuction assisted circumferential trimming technique is proved reliable and safe in treatment for axillary osmidrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Tumescent anesthesia is in favor of subcutaneous undermining and minimize the risk of hemorrhage with the combined application of epinephrine. 17 Hematoma has great influence on the effectiveness and safety of surgery. Strict hemostasis and drainage are the keys to preventing hematoma formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumescent anesthesia is in favor of subcutaneous undermining and minimize the risk of hemorrhage with the combined application of epinephrine. 17 Hematoma has great influence on the effectiveness and safety of surgery. Strict hemostasis and drainage are the keys to preventing hematoma formation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the application of appropriate tumescent anesthesia also helps to protect the subdermal vascular network. Tumescent anesthesia is in favor of subcutaneous undermining and minimize the risk of hemorrhage with the combined application of epinephrine 17 …”
Section: Discussionmentioning
confidence: 99%
“…Since 1999, we have used the surgical method of trimming and coagulating the apocrine glands under direct vision through double incisions parallel to axillary creases to treat primary AO. Subsequently, with the development of small-incision minimally invasive technology and improvement in instruments, for patients with AO who undergo surgery for the first time, we gradually switched to small-incision minimally invasive surgery such as small-incision curettage, liposuction curettage, and liposuction trimming 15 . On the other hand, in patients who relapse after the primary surgery, we still use the method of trimming and electrocoagulation to remove and destroy the apocrine glands under direct vision through double incisions parallel to axillary creases.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure uses negative pressure to repeatedly suck and scrape the subcutaneous tissue with a liposuction needle to damage the sweat glands after using tumescent anesthesia in the armpit area. A study conducted by Hu X. et al [9] reported a positive outcome rate of 94.9% and a patient satisfaction rate of 93.7% among 79 patients after a 12-24 months follow-up. There were a few notable complications, including 3 cases of subcutaneous hematoma and 4 cases of localised skin necrosis.…”
Section: Aspiration With Negative Pressure In Axillary Subcutaneous S...mentioning
confidence: 98%